Limestone Diagenetic Records Based on Petrographic Data of Sentolo Formation at Hargorejo Traverse, Kokap, Kulonprogo - Sigit Maryanto (Geological Agency, 2012)
DOI: 10.17014/ijog.v7i2.138Limestone diagenetic records of Sentolo Formation have been studied in order to trace the history of the geological processes after the deposition of the rocks. A stratigraphic measure traverse was made in Hargorejo Village, Kulonprogo District, to identify the petrological characteristics of the Sentolo Formation. Limestone samples were taken along this traverse, and were used for a petrographic analysis. The analysis of thirtyeight limestone samples shows that the type is dominated by bioclastic grainstones which have been affected by various kinds of diagenetic processes after the deposition. The diagenetic processes recorded under the polarization microscope include cementation, replacement, bioturbation, micritization, recrystallization, dolomitization, compaction, fracturing, and leaching.